SOLANUM TORVUM DAN BIOAKTIVITASNYA - Silalahi, Marina (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2019)
Solanum torvum is a plant originates from America Latin, but has long been cultivated in Indonesia. Ethnobotany of S. torvum is used as a medicine for fever, wounds, dental disorders, reproductive system disorders, and hypertension, asthma, diabetes mellitus, eye disorders, and intestinal disorders. This article was written based on a study of various scientific articles published online and offline, to explain the bioactivities of the S. torvum associated with its use. Solanum torvum has bioactivity as anti-fungal, anti-bacterial, anti-diabetes mellitus, hepatoprotective, anti-ulcer, and analgesic. The ability of S. torvum as an antimicrobial is very potential to be used as a natural food preservative and also as a medicine for various microbial infections.